Secret Agent Jack Stalwart. [book 4], The Caper of the Crown Jewels : Great Britain - Singer Hunt, Elizabeth (Red Fox, 2006)
Some of Great Britain's most prized possessions, the Crown Jewels, have vanished from the Tower of London. Can Secret Agent Jack Stalwart triumph in his battle against a master magician to save the jewels before they go missing for ever?